2006
DOI: 10.1007/s00432-006-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined profile of the tandem repeats CAG, TA and CA of the androgen and estrogen receptor genes in breast cancer

Abstract: Our results confirm previous reports regarding an association between longer CAG repeats and breast cancer. In addition to that, we found that the combination of long CAG, short TA and CA repeats are strongly associated with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
1
14
0
2
Order By: Relevance
“…Several case-control studies have examined the length of the CAG repeat stretch to check for an association with breast cancer risk [reviewed by the authors in 10, 27-32] ( Table 3). Out of 20 such studies (including the present study), six presented direct association of longer CAG stretch (greater number of repeats) with increased breast cancer risk in American [27,33], Canadian [34], Romanian [35], Spanish [36], and Taiwanese [37] women. At least two studies reported a reduced disease risk with smaller repeat length in Canadian women [30,38], showing a direct relation between repeat length and disease risk.…”
Section: Discussionmentioning
confidence: 96%
“…Several case-control studies have examined the length of the CAG repeat stretch to check for an association with breast cancer risk [reviewed by the authors in 10, 27-32] ( Table 3). Out of 20 such studies (including the present study), six presented direct association of longer CAG stretch (greater number of repeats) with increased breast cancer risk in American [27,33], Canadian [34], Romanian [35], Spanish [36], and Taiwanese [37] women. At least two studies reported a reduced disease risk with smaller repeat length in Canadian women [30,38], showing a direct relation between repeat length and disease risk.…”
Section: Discussionmentioning
confidence: 96%
“…receptor gene and the risk of breast cancer. Others however, have shown an association between the presence of short [27][28][29] or long [30][31][32][33][34][35][36][37] alleles containing CAG repeats in the AR gene and an increased incidence of breast cancer. For example, Yu et al [38] indicated that longer CAG repeats in the AR gene are associated with lower grade of tumors, fewer lymph node metastases and longer survival.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that CA repeat contraction in the microsatellites located in the ADAMTS9 promoter may block RNA polymerase binding to the ADAMTS9 promoter. If this scenario is correct, cancer-related gene expression, such as that of ADAMTS9, in tumors would decrease (15,16), and lower matrix metalloproteinase activity would translate into a reduced ability to invade lymphatic vessels and metastasize. Porter et al reported that the expression of ADAMTS9 in breast cancer tissues was down-regulated with respect to noncancerous breast tissues and uncovered a potential association between ADAMTS9 and breast cancer (17).…”
Section: Discussionmentioning
confidence: 99%